How I migrated from Venezuela to Costa Rica: certainties and uncertainties. Testimony as a necessary tool to problematize the Costa Rican institutionality in terms of migratory processe - Palma Chacón, Jimena (2020)
The sustained increase in mobilizations from Venezuela to Costa Rica appears as a highly complex phenomenon, the revision of which has quickly exhausted the traditional categories of analysis. This is why, from a human rights perspective, this article is based on the story and experience of the migrant as a necessary tool to highlight the shortcomings and limitations of the Costa Rican institutional framework that embraces individuals mobilized from Venezuela.  Access to human rights, for example, guarantee to due process and information, and even the right to migrate (or not to be forced to do so) is questioned from the experience narrated by Andreina, who migrated to Costa Rica seeking to improve her quality of life and whose experience is vital to deconstruct the discourse that has been perpetuated by the institutions that regulate the access of migrants and by the State as guarantor of human rights.  Both the geopolitical analysis of the Venezuelan context, as well as the analysis of her story, manage to materialize the structural and cultural violence that are reproduced by the institutional framework and public policies designed to contain the growing human mobilization throughout Latin America.